THE TEACHING OF ENGLISH TO THE FIRST YEAR STUDENTS OF SMP N 2 SRAGI PEKALONGAN - HIDAYAH, SRI (2010)
This research aims at describing (1) the implementation of the teaching of English focused on (a) the objective of English teaching, (b) materials of teaching, (c) classroom activities, (d) the roles of the students, the teacher, and materials, and (2) knowing the problems faced by the teacher in implementing teaching English. The writer takes the English teacher and students of the first year as the subject of the study. The data of the study are by observing the English class, document in collected, and interviewing the English teacher and some students of the first year of SMP N 2 Sragi Pekalongan. Based on the research finding, the writer draws some conclusions. First, the objective of English teaching is developing communicative competence both in written and oral forms. Second, the teacher uses the material that is appropriate with the syllabus of School level-based curriculum. Third, the implementation of the English teaching by the teacher is very simple on how the material can be transferred. Fourth, the roles of the teacher, the students, and the material can not be played maximally. The teacher's roles as transfer of knowledge, drillmaster, controller, motivator, observer, and director. The students roles are as performer and listener. While the material's role is teaching media which help the teacher giving instruction or information to the students. Fifth, there are four problems faced by the teacher, namely classroom management, limited time, different capability of the students, and unstable motivation of the students.